2018
DOI: 10.1111/acem.13640
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Implementation of a Novel Management Protocol Increases the Outpatient Treatment of Pulmonary Embolism and Deep Vein Thrombosis

Abstract: Objective: The objective was to determine whether a protocol combining risk stratification, treatment with the direct-acting oral anticoagulant rivaroxaban, and defined follow-up is associated with a greater proportion of patients with venous thromboembolism (VTE) treated as outpatients, without hospital admission. Methods:We performed a multicenter study of patients diagnosed with VTE (pulmonary embolism [PE] or deep vein thrombosis [DVT]) in two urban EDs, 18 months before and 18 months after implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…Effective and safe treatment of patients with PE in the outpatient setting requires patient education and robust follow‐up pathways. One recent US multicenter study demonstrated that the implementation of a treatment protocol that combined risk stratification, anticoagulation treatment with rivaroxaban, and well‐defined procedures for follow‐up of patients with DVT or PE increased the rates of patients treated as outpatients without increasing rates of adverse outcomes . Another multicenter US study evaluated the use of an integrated electronic clinical decision support system for risk stratification and on‐site decision making for identifying patients suitable for outpatient treatment of PE.…”
Section: Education and Follow‐up Of Patients With Pulmonary Embolism mentioning
confidence: 99%
“…Effective and safe treatment of patients with PE in the outpatient setting requires patient education and robust follow‐up pathways. One recent US multicenter study demonstrated that the implementation of a treatment protocol that combined risk stratification, anticoagulation treatment with rivaroxaban, and well‐defined procedures for follow‐up of patients with DVT or PE increased the rates of patients treated as outpatients without increasing rates of adverse outcomes . Another multicenter US study evaluated the use of an integrated electronic clinical decision support system for risk stratification and on‐site decision making for identifying patients suitable for outpatient treatment of PE.…”
Section: Education and Follow‐up Of Patients With Pulmonary Embolism mentioning
confidence: 99%
“…8 The keys to safe and effective outpatient treatment are appropriate risk stratifications and close follow-up arrangements. 4 In this external validation, the modified HOPPE score performed well, with very high NPV for in-hospital mortality and the composite outcomes of in-hospital mortality and non-fatal MACE. It showed similar predictive performance to the sPESI score for the composite outcome of in-hospital mortality and non-fatal MACE.…”
Section: Discussionmentioning
confidence: 77%
“…Outpatient treatment of venous thromboembolism (including, PE and deep venous thrombosis) is becoming more common. 4 Outpatient treatment releases capacity in hospitals, reduces patient exposure to hospital-acquired infections and other complications associated with hospitalization and is associated with high levels of patient satisfaction. 8 The keys to safe and effective outpatient treatment are appropriate risk stratifications and close follow-up arrangements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations